Node Identification Using Inter-Regional Correlation Analysis for Mapping Detailed Connections in Resting State Networks - Sohn, William S.; Lee, Tae Young; Yoo, Kwangsun; Kim, Minah; Yun, Je-Yeon; Hur, Ji-Won; Yoon, Youngwoo Bryan; Seo, Sang Won; Na, Duk L.; Jeong, Yong; Kwon, Jun Soo (Frontiers in Neuroscience, 2017)
Brain function is often characterized by the connections and interactions between highly interconnected brain regions. Pathological disruptions in these networks often result in brain dysfunction, which manifests as brain disease. Typical analysis investigates disruptions in network connectivity based correlations between large brain regions. To obtain a more detailed description of disruptions in network connectivity, we propose a new method where functional nodes are identified in each region based on their maximum connectivity to another brain region in a given network. Since this method provides a unique approach to identifying functionally relevant nodes in a given network, we can provide a more detailed map of brain connectivity and determine new measures of network connectivity. We applied this method to resting state fMRI of Alzheimer’s disease patients and found decreased connectivity within the default mode network. These results validate our method since they are in agreement with previous resting studies. In addition, new measure of network connectivity revealed a more detailed description of how the network connections deteriorate with disease progression. This suggests that analysis using key relative network hub regions based on regional correlation can be used to detect detailed changes in resting state network connectivity.